Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan (Studi pada Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Nofriyanti , Lola; Rahmi, Fitria (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
The purpose of this study was to determine the effect of capital structure and profitability on firm value. The population in this study was manufacturing companies, especially the food and beverage subsector which listed on the Indonesia Stock Exchange period 2013-2017. This study uses multiple regression models on panel data to determine the effect of capital structure and profitability on firm value. The capital structure indicator in this study is the Debt to Equity Ratio (DER), the profitability indicator in this study is the Return on Equity Ratio (ROE) while the firm value indicator uses a Price to Book Value (PBV) as a proxy. Based on the results of this research analysis using panel data regression which was processed with Stata v.12 shows that Capital Structure (DER) and Profitability (ROE) has an significant effect on Company Value (PBV)